Employment Choices and Pay Differences between Non-Standard and Standard Work in Britain, Germany, Netherlands and Sweden - Siv Gustafsson; Eiko Kenjoh; Cecile Wetzels (Tinbergen Institute, 2001)
This paper analyses two questions. First, how do otherwise similar people across four countries end up in fourdifferent employment states: 1) full-time with a regular contract, 2) part-time with a regular contract, 3) fixedterm contract full-time or part-time and 4) self-employed? Second, how do wages differ between otherwise similarpeople between work arrangements in each of the four countries in our analysis? We employ the 1998 wave ofhousehold panel data sets namely BHPS for Britain, GSOEP for Germany, OSA for the Netherlands and HUS for Sweden.The reason for analysing and comparing four countries is an interest in policies that may result in differentchoices for otherwise similar people.Our multinomial analyses show that the probability of working part time, both for men and women in the Netherlandsis much higher other things equal than for men and women in the other three countries. Similarly the probabilityof being self employed for men in Sweden is much higher than in the other three countries. In Germany, fixed-termworkers are conspicuously badly paid compared to fixed-term workers in the other three countries. Furthermorewe find part-time workers relatively better paid in Sweden and the Netherlands than in Britain and Germany.
Keywords: 330; Arbeitszeitgestaltung; Teilzeitarbeit; Berufswahl; Arbeitsbedingungen; Lohnstruktur; Vergleich; Großbritannien; Deutschland; Niederlande; Schweden